SURFACE AREA AND VOLUME OF A PRISM (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
Prisms are fundamental geometric shapes that have a wide range of applications in both theoretical mathematics and practical fields like architecture, engineering, and manufacturing. A prism is defined as a polyhedron with two parallel, congruent bases and rectangular lateral faces. This article explores the methods for calculating the surface area and volume of a prism, including the influence of base shapes and the height of the prism. It also discusses the practical applications of these calculations in various industries.